2003
DOI: 10.1034/j.1600-6143.2003.00094.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of the Immunosuppressant Sirolimus Against Aortic Atherosclerosis In Apo E-Deficient Mice

Abstract: Atherosclerosis is a chronic inflammatory disease that develops in response to injury to the vessel wall, and is augmented by hypercholesterolemia. To further delineate the role of the immune system and local factors in this process, we assessed the effects of the immunosuppressant sirolimus (Rapamycin, RAPAMUNE â , Wyeth, Collegeville, PA) on atherosclerosis in the apoE-deficient (apoE KO) mouse, a well-accepted model of cardiovascular disease. ApoE KO mice were fed a high fat diet and sirolimus was administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
84
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 63 publications
6
84
0
1
Order By: Relevance
“…We observed that orally administered rapamycin increased total cholesterol levels in apoE-deficient mice fed a normal rodent diet compared with untreated animals. Interestingly, when hypercholesterolemia in apoE-deficient mice is severely aggravated by a high-fat supplemented diet, the hypercholesterolemic effect of rapamycin has been observed by some (22) but not by others even with the use of a high-dose, long-term rapamycin treatment (13,23,24). Importantly, our result obtained in this murine model of spontaneous atherosclerosis agrees with the general clinical concept that the increase in cholesterol is a side effect of rapamycin treatment (25).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We observed that orally administered rapamycin increased total cholesterol levels in apoE-deficient mice fed a normal rodent diet compared with untreated animals. Interestingly, when hypercholesterolemia in apoE-deficient mice is severely aggravated by a high-fat supplemented diet, the hypercholesterolemic effect of rapamycin has been observed by some (22) but not by others even with the use of a high-dose, long-term rapamycin treatment (13,23,24). Importantly, our result obtained in this murine model of spontaneous atherosclerosis agrees with the general clinical concept that the increase in cholesterol is a side effect of rapamycin treatment (25).…”
Section: Discussionsupporting
confidence: 81%
“…There is a consensus that rapamycin significantly reduces the aortic atherosclerotic plaque in apoE-deficient mice fed a fat-rich diet (12,13,22,23,26). In the present study, we also observed similar anti-atherosclerotic effects of rapamycin administered to the apoE-deficient mice fed a normal rodent diet.…”
Section: Discussionsupporting
confidence: 77%
“…[16][17][18] However, several studies also suggest that cell-cycle inhibitors may possess antiatherogenic properties. [19][20][21][22][23] Although published data are conflicted, it appears that overall outcomes, including target vessel revascularization rates, are slightly more favorable in patients receiving DES, although this has to be weighed against higher stent costs and the necessity for prolonged, uninterrupted antiplatelet therapy. 24,25 In addition, there are differences in the rates of target vessel versus target lesion revascularization rates, implying that pathologic processes are modified in other regions of the stented coronary.…”
Section: Resultsmentioning
confidence: 99%
“…16,17 Multiple studies have demonstrated the atherosclerotic attenuation of sirolimus in Apolipoprotein E-deficient mice and human vascular smooth muscle cells. [19][20][21][22] A variety of studies investigating coronary artery disease in heart transplant patients, who have baseline endothelial dysfunction, have shown that antiproliferatives such as sirolimus attenuate the rate of atherosclerotic progression. 29,30 In addition, paclitaxel is a well-known immunomodulatory agent and has also been associated with atherosclerotic regression in animal models, as well as reduced inflammation in stented porcine arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the mTOR signalling pathway has been identified as a therapeutic target 39, 40. Rapamycin and its analogues are widely used in preventing restenosis and suppressing atherosclerosis 41. Jahrling et al21 showed that rapamycin‐mediated mTOR attenuation decreased the atherosclerosis lesion area in high‐fat‐fed LDLR−/− mice.…”
Section: Discussionmentioning
confidence: 99%